UJI AKTIVITAS ANTIOKSIDAN EKSTRAK BIJI KAPUK RANDU (Ceiba pentandra (L) Gaertn) DENGAN METODE DPPH - Ariyanis Salma; Endang Setyowati; Fahrudin Arif (Nusantara Hasana Journal, 2025)
Kapuk randu (Ceiba pentandra (L). Gaertn) is a plant that is widely found in Indonesia and has long been used in traditional medicine. The seeds of this plant are known to contain various secondary metabolite compounds such as alkaloids, flavonoids, saponins, tannins and phenolics that have the potential to be antioxidants. This study aims to identify the compounds contained in randu kapok seeds and evaluate their potential antioxidant activity. The research method involves the extraction of kapuk seeds using maceration with 70% ethanol solvent. Furthermore, qualitative phytochemical screening is carried out to identify groups of compounds such as alkaloids, saponins, flavonoids, tannins, and phenolics. The antioxidant activity test was carried out using the DPPH method with concentration variations of 40, 80, 120, 160, and 200 ppm. The results of phytochemical screening showed that randu kapok seed extract was positive for alkaloid and flavonoid compounds. Antioxidant activity testing yielded an average IC50 value of 276.5 μg/mL. Based on categorization, the IC50 value indicates that randu kapuk seed extract has very weak antioxidant activity.